An experimental study on the influence of instructional mobile applications in enhancing listening comprehension of rural students in India - Raj, Antony; Tomy, Prajeesh (Frontiers in Education, 2024)
Mobile learning is a vital approach to language teaching and learning because of its accessibility, portability and variety of resources. It offers real-life language use with synchronous learning, flexibility and an opportunity to engage with the global community. It allows learners to practice language skills from anywhere. Mobile apps provide interactive and encouraging continuous language skill improvement. This study aimed to implement the use of linguistic instructional mobile applications in language classrooms and investigate its effectiveness on the listening comprehension levels of Indian rural students. M-learning has made significant progress in recent years and is increasingly being used in the language teaching and learning process. Pedagogic Mobile applications were opted in this study for language teaching and also to promote selflearning among the participants. To assess the method's instructional impact, an experimental study was conducted with (n=149) tertiary-level students from various rural colleges in Tamil Nadu, India. The participants of the study were divided into two groups: a Control Group (n=75) and an Experimental Group (n=74). To determine the significance of the intervention, pre and post-tests were conducted to compare the participants' listening comprehension levels in both groups. Different types of audio files were used in the intervention to improve the listening skills of the Experimental group. The demographic factors of the participants such as gender, locality, and parental income were regarded as significant variables of the study since the participants were from different infrastructures and from different socio-economic backgrounds. Statistical analysis including paired t-tests, independent t-tests, and ANOVA (analysis of variance) was done to determine the impact of intervention and differences between social groups. The results proved that rural backgrounds students were able to overcome language barriers through the use of mobile applications.